Main characteristics, theoretical issues of effective management strategies in higher education - Levakov Izzatulla Nematillaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In world practice, the economic activity of higher education institutions has traditionally been considered in a certain external framework with certain rules of the economic situation. At the same time, micro and macro level analysis of economic effects has been created. Economic diagnostics related to the analytical preparation of management decisions and their quality improvement is a new direction of management analysis. In general, economic diagnosis arose as a result of the need to dramatically improve the quality of management and is directly related to the implementation of an innovative development strategy.